Assessing the impact of body mass index on insulin resistance and metabolic risk factors in pre-diabetic individuals: A comprehensive cross-sectional study - Satyanarayana Raju P,; Pyda Vijaya Radhika,; Ch. BS Srinivas,; Ritu Vaish,; Usha Rani P, (Asian Journal of Medical Sciences, 2024)
Background: Insulin resistance plays a crucial role in the onset of type 2 diabetes, with body mass index (BMI) being a significant determinant. Aims and Objectives: This study examines the link between BMI and insulin resistance in pre-diabetic individuals to inform strategies for early diabetes intervention. Materials and Methods: This cross-sectional study involved 100 pre-diabetic participants. Data on demographic characteristics, BMI, insulin resistance (measured by the Homeostatic Model Assessment for Insulin Resistance, HOMA-IR), lipid profiles, and blood pressure (BP) were collected. Participants were categorized into normal weight, overweight, and obese groups to explore the relationship between BMI and insulin resistance and its impact on metabolic and cardiovascular health. Results: The average participant age was 45.8 years (SD=12.3), with a slight majority being female (52%) and an average BMI of 28.4 kg/m² (SD=4.5). A significant positive correlation (r=0.64, P<0.001) between BMI and the HOMA-IR index highlighted the association between increased BMI and insulin resistance. Obese individuals had a notably higher HOMA-IR index (3.5±1.3) compared to those overweight (2.5±1.0) and of normal weight (1.9±0.8). In addition, the study found worsening lipid profiles and increased BP with higher BMI categories. Gender did not significantly affect insulin resistance, whereas a slight increase in HOMA-IR with age was noted (r=0.23, P=0.02). Conclusion: The findings highlight the strong correlation between higher BMI and increased insulin resistance in pre-diabetics. They emphasize the importance of managing body weight to mitigate the risk of diabetes and cardiovascular diseases.